The Ombudsman as a Manifestation of Passive Transparency in the Special Social Security Regime of the Municipalities of Rio de Janeiro State ("Revista Gestión y Conexiones", 2024)
We identify how the Special Social Security Regime (RPPS) Ombudsman of municipalities of Rio de Janeiro State falls under the level I certification of the RPPS Pro-Management Program, in the indicator related to the Ombudsman; a tool to promote the democratic participation of citizens through passive transparency. The relevance of this study stems from the fact that the RPPS are in charge of managing a substantial number of resources, having managed around 157 billion Reais in investments for their respective insureds in 2020 (SPREV, 2021). Through documental analysis performed on the websites of the Rio de Janeiro RPPS and their respective federative entities, we concluded that among the 92 municipalities in the State, only 79 have RPPS. Furthermore, 54.4% of municipalities have a communication channel in the RPPS, while 43.1% have it available through the Federal Entity to which they are linked, and 2.5% have no such communication channel. Thus, we state that most RPPS has given due importance to the RPPS Pro-Management Manual, specifically regarding the accomplishment of the goal of providing more transparency to the relationship between the insured and society.